Dynamic contrast-enhanced MRI analysis for prognosis of intracranial dissecting aneurysm with intramural haematoma after endovascular treatment: an observational registry study. Issue 1 (1st July 2020) - Tian, Zhongbin; Wang, Zhongxiao; Li, Wenqiang; Zhu, Wei; Liu, Jian; Zhang, Ying; Yang, Xinjian; Zhang, Yisen
Abstract : Background and purpose: Intracranial dissecting aneurysm (IDA) with intramural haematoma (IMH) is an intractable cerebrovascular disease. The outcome of IDA with IMH after endovascular treatment varies across different individuals: some IMHs stop growing after endovascular treatment, while others continue to grow, even after embolisation of the parent artery. Currently, the mechanism for the continuous growth of IMH after endovascular treatment is still unclear. Continuous haemorrhage of the vasa vasorum in the IMH is considered to be associated with continuous enlargement of the IMH; however, this theory has not been proved by in vivo imaging. Methods and analysis: This study will establish a prospective cohort of 80 patients who had an IDA with IMH and received endovascular treatment. Demographic characteristics, IDA morphological characteristics and treatment characteristics will be collected prospectively. All patients will undergo dynamic contrast-enhanced MRI (DCE-MRI) before and 6 months after the endovascular treatment. According to the follow-up results of the MRI, the IDAs will be divided into two groups: a haematoma stabilisation group and a haematoma enlargement group. Then, quantitative analysis of the vasa vasorum in the IMH will be performed, and differences between the two groups will be compared with determine the association between DCE-MRI related parameters and the outcomes of IMH changes. Ethics and dissemination: The research was approved by the ethics committee of Beijing Tian Tan Hospital (KY 2019-024-03) and written informed consents would be obtained from all patients included in this study. The results of this study will be disseminated in professional printed media. Trial registration number: NCT03940859 . Registered: 7 May, 2019. https://clinicaltrials.gov/ct2/show/NCT03940859 .